The in-vitro and in-vivo metabolism of the anabolic steroid bolasterone by LC-MS/MS and GC-MS/MS - Muresan Anca Raluca; RAHAMAN KHANDOKER ASIQUR; FARZANA BINTE RAFIQUE; Kwon, Oh-Seung (한국분석과학회, 2020)
PT-004 The in-vitro and in-vivo metabolism of the anabolic steroid bolasterone by LC-MS/MS and GC-MS/MS Anca Raluca Muresan1,2, Khandoker Asiqur Rahaman1,2, Farzana Binte Rafique1,2, and Oh-Seung Kwon1,2,,; 1Doping Control Center, Korea Institute of Science and Technology, Seoul, 02792, Korea, 2Division of Bio-Medical Science & Technology, KIST School, Korea University of Science and Technology, Seoul 02792, Korea; Corresponding author: oskwon@kist.re.kr Bolasterone (7α,17α-dimethyltestosterone) is a typical steroid drug that is illegally used in different kinds of sports disciplines. Identification of phase I and II metabolites is a useful tool for the confirmation of various metabolic pathways in order to develop long-term biomarkers for anti-doping analysis. This study aims to investigate phase I and phase II metabolites of bolasterone (MW 316) through both in-vitro (rat liver microsome) and in-vivo (urine after oral administration to rats) experiments. The metabolites were identified by high resolution LC-MS/MS and GC-MS/MS. By the LC-MS/MS analysis, a total of 16 metabolites (15 phase I and 1 phase II) were identified. In-vitro were found 6 mono-hydroxylated (M8-M13 as m/z 333 of [M+H]+), 5 di-hydroxylated (M1, M5-M7, M14 as m/z 493 of [M+H]+), along with 1 resulting from reduction (M15, as m/z 285 of [M+H-2H2O]+), and 1 glucuronide metabolite (M16, as m/z 493 of [M+H]+). In-vivo, a total of 8 di-hydroxylated metabolites (M1-M7, M14 as m/z 349 of [M+H]+) were found. The plausible structures are tentatively identified as: mono-hydroxylation at the A ring (M12), B ring (M8), and D ring (M9, M10, and M11). Reduction at 3-keto and Δ4 (M15), and conjugation with glucuronic acid at D ring (M16). By GC-MS/MS analysis, a total of 7 in-vitro metabolites were found as 3 mono-hydroxylated (m1-m3 as M+=548), 1 mono-hydroxylated and 1 reduction (m4 as M+=546), and 3 di-hydroxylated (m5-m7 as M+=636).
Keywords: in vivo; in vitro; metabolism; rat; urine; LC-MS/MS